Physicochemical and methemoglobin quantification analyzes of tucupis sold in the Metropolitan Region of Belém/PA (Research, Society and Development, 2023)
Tucupi is a yellowish extract, obtained from the processing of cassava and a derivative rich in nutrients, however toxic substances such as hydrocyanic acid can be found in its composition. Consumption of this product with high levels of HCN can result in health problems causing severe pathologies. Its concentration will depend on the processing the tucupi is subjected to, aiming to guarantee its food safety through adequate quality control. This work aimed, through an experimental study, to carry out organoleptic, physical-chemical and methemoglobin quantification analyzes in tucupi samples sold in open-air markets in Belém/PA. In the methodology, toxicological tests were used to identify the formation of methemoglobin in blood samples, physical chemical tests such as titratable acidity (11.13; 10.56; 10.56 NaOH/100mL), ash (1.79%; 0.86 ; 0.75%), total solids (4.8; 3.4; 3.4), pH (4.05; 4.403; 4.1), color (∆E: 53.4; ∆E: 56, 6; ∆E: 52.7); and humidity (95.19%; 75.30%; 95.04%). Based on the results obtained in the tests and their comparison with the values established by sanitary standards, it is necessary to standardize the process of obtaining this food, with effective quality control and supervision, with the aim of reducing the risk of poisoning through consumption. of tucupi sold in the northern region.